NEWS FRAMING ANALYSIS OF BAGYO WAHYONO-FX SUPARJO IN THE 2020 MAYORAL ELECTION AT SOLOPOS.COM AND TRIBUN SOLO.COM - St Arief Setiaji; Heri Budianto (MediaKom : Jurnal Ilmiah Komunikasi, 2021)
Rural election in Solo presented an interesting political competition between the Gibran Rakabuming Raka-Teguh Prakosa and Bagyo Wahyono-FX Suparjo. The two couples come from different political 'castes'. Through research with an approach approach using the Robert N. Entman framing analysis model, it can be seen the mass media framing model in revealing that Bagyo Wahyono-FX Suparjo couple who came from independent candidate. Meanwhile, in democratic parties, such as local elections, the mass media are in a neutral position.